Referencias indicativas de los procesos de cambio territorial en un espacio de montaña (Sector Central de la Montaña Cantábrica) - Delgado Viñas, Carmen; Gil de Arriba, Carmen; Hortelano Mínguez, Luis Alfonso; Plaza Guitérrez, Juan Ignacio (Geographicalia, 2016)
This contribution wants to meditate on the processes of territorial transformation that have been developed in the last decade of the XX century on a mountain space (central sector of the Cantabrian Mountain range: Mountain Palentina and South of Cantabria). Study the own territory as main object of analysis starting from the formulation of some previous propositions that they guide this contribution: changes in the administration of the territory; changes in the own image of these mountain spaces; changes in the conceptualization and "functionality" assigned to this space inside the new models and ordination proposals and territorial development; and changes, also, in the forms and structures of internal territorial organization. To develop these general orientations they will be analyzed, in the first place, the most remarkable factors that have caused the pointed transformations and, next, you will proceed to highlight the main addresses and manifestations of the produced changes.